Flood-Irrigated Wheat Cost-Return Budget - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on flood-irrigated wheat production.
MF590_1996_10
Keywords: MF590; Economics; Crops; MF